Hukou, Migration, Strain, and Crime: A Case of Incarcerated Population in China - Qu, Jia (Crime & delinquency, 2025)
Based on survey data from 1,593 prisoners in Guizhou, China, the current study examines the influence of hukou and migration status on crime involvement. Utilizing the general strain theory framework, this study tests a mediation model that hukou (urban vs. rural) and migration status (migrant vs. local) intersect to shape people’s experience of strain, which further leads to engagement in crime. Among the strain variables, victimization stands out as the most significant mediator that connects rural hukou to crime. These results suggest that the Chinese government should completely abolish the household registration system, or at least make more effective reforms that provide more equal opportunities for development and safety protection to people with rural hukou.